Update on the Management of Thyroid Disease during Pregnancy - Yim, Chang Hoon (Endocrinol Metab (Seoul), 2016)
Thyroid dysfunction during pregnancy can result in serious complications for both the mother and infant; however, these complications can be prevented by optimal treatment of maternal overt thyroid dysfunction. Although several studies have demonstrated that maternal subclinical hypothyroidism is associated with obstetric complications and neurocognitive impairments in offspring, there is limited evidence that levothyroxine treatment can improve these complications. Therefore, most professional societies do not recommend universal screening for thyroid dysfunction during pregnancy, and instead recommend a case-finding approach in which only high-risk women are tested. However, recent studies have estimated that targeted thyroid function testing misses approximately 30% to 55% of hypothyroidism cases in pregnant women, and some associations and researchers have recommended universal screening of pregnant women to facilitate the early detection and treatment of overt hypothyroidism. This review summarizes recent data on thyroid function test changes, thyroid functional disorder management, and thyroid screening during pregnancy.